Imperfect Tacit Collusion and Asymmetric Price Transmission - Muhammed Bulutay; David Hales; Patrick Julius; Weiwei Tasch (ZBW - Leibniz Information Centre for Economics, 2021)
We investigate the role tacit collusion plays in Asymmetric Price Transmission (APT), the tendency of prices to respond more rapidly to positive than to negative cost shocks. Using a laboratory experiment that isolates the effects of tacit collusion, we observe APT pricing behavior in markets with 3, 4, 6, and 10 sellers, but not in duopolies. Furthermore, we find that sellers accurately forecast others' prices, but nevertheless consistently set their own prices above the profit-maximizing response, particularly in the periods immediately following negative shocks. Overall, our findings support theories in which tacit collusion plays a central role in APT.
Keywords: D43; L13; C92; C72; C73; 330; Asymmetric Price Transmission; Tacit Collusion; Oligopolistic Competition; Market Power; Rockets and Feathers